The Reality Of Fiscal Policy In Syria Between 2011 And 2019 - إدلبي منى; فاضل حسن (Latakia University Journal - Economic and Legal Sciences Series, 2021)
In the normal circumstances of any country in which the fiscal policy is based on increasing public expenditures, reducing taxes and reducing the state’s general budget deficit, with the aim of stimulating the demand for goods and services needed by society. A real threat to the stability of the situation of public financial policy in Syria.. When talking about financial and economic reform, real reconstruction and reducing the budget deficit, there must be a realistic fiscal policy represented in how to work to increase the available public revenues due to the growing need for public spending and thus work to reach a balance between them as much as possible or reduce the large gap between them at the present time, especially After a major part of the state’s revenues came out of covering public expenditures, represented by the exit of the oil sector and some strategic crops such as cotton from the state budget after terrorist groups took control of them